The Impact of Flow Patterns Due to the Cold Lahar Flooding of Mount Semeru on the Collapse of the Bridge Connecting Malang District and Lumajang District - Djoni Irianto; Nur Andajani; Nurmi Frida; Andang Wijaya; Heri Suryaman; Desy Ratna Arthaningtyas; Arvieka Sabilla Putri Setiadi; Muhammad Evanni; Naufal Dhiya U (Engineering And Technology Journal, 2024)
The flow patterns that occur in rivers as a result of falling cold lava often cause damage here and there. This incident cannot be separated from the large volume of water mixed with material that crosses the open channel which is caused by input water supply or water supply from river reservoirs crossed by cold lava. by water researchers for water mixed with volcanic eruption material suspended above. The event of water flowing through a river is influenced by the presence of the surface profile of the river bed and the various widths of the river that occur. If a volume with a certain viscosity is given, a thick flow will be formed that can be seen on the surface of the river, while that which is not visible to the naked eye above the water surface is called thick viscosity. If the runoff of cold lava material that occurs in the channel is not measured, it will result in wild jumps. The wild and viscous jumping structure that has been arranged can be observed as to how the flow pattern occurs. To avoid not detecting the flow pattern, water measuring structures are needed, one of which is a threshold with openings below or what is known as flow above the threshold along with existing bridge buildings around it. This sluice gate is easy to operate manually. The need for water operations with excess water availability is not an easy thing to calculate, because of the influence of depth and jumps that occur around the bridge, hydraulic jump patterns often ignore this measurability, this will be an obstacle if there is a large supply of cold lava. mixed with rainwater during peak conditions in the drainage process. Observations of this completion need to be proven by carrying out model tests using a tool known as the Threshold which produces a water jump along with the material. This requires further investigation for research in the model channel. For modeling thresholds and bridges connecting between plains, this tool provides instruments and many threshold treatments as well as regulating pressurized water with a pump at a certain flow rate in a measurable manner. To analyze the height of building damage, determine the flow pattern, speed by observation, test results with valve openings on certain pumps, researchers tested and measured the position of cold lava deposits one by one, the position of the slope of the river in certain sections, starting with an opening of 0.5; 0.75, read the instrument, move the threshold position from a bridge distance of 20 cm, 40 cm, to the furthest distance of 240 cm. Make graphs of test results for the threshold of the bridge opening transfer tool by testing the tool and opening 3 times for each pump opening, recording, mapping the depth values, jump length and travel time of the instrument on the test tool. Recommend the results of the analysis of the Threshold and Bridge tests to provide information to bridge construction planners that the test results with various threshold positions in certain conditions have the value of the Glidik II bridge collapse, the jump with the travel time of the speed of passing cold lava. Next, the bridge is determined and the next threshold can be used to determine how severe the damage is to the river. This research is laboratory research with threshold and bridge models. The target of this output is a journal article resulting from a simulation of determining the flow pattern that occurs in the channel by shifting the position of the threshold relative to the location of the bridge from the channel model with various diameter sizes of the model material, the results of which are in the form of a table and graphed on the part modeled in the water laboratory, especially flow with sediment and cold lava material. The results of this section were observed up to the collapse of the bridge at a depth of 4.5 cm with an opening of ½ second to 37 (on the model scale) observed or a depth of 45 meters (on the empirical scale). to then be written in the form of an article to be included in an international journal.